2013
DOI: 10.1111/iej.12122
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two intracanal dressings in adult Portuguese patients: a qPCR and anaerobic culture assessment

Abstract: Infected root canals contained a high bacterial load, and the chemomechanical root canal preparation reduced bacterial equivalents by 99.1% and anaerobic counts by 98.5%. Intracanal dressings were not efficient at reducing bacterial load, but the 14-day intracanal dressing with Ca(OH)2 performed significantly better than CHX, particularly in cases with apical periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
4
0
0
8
Order By: Relevance
“…The rDNA-based analysis showed that the inter-appointment medication did not contribute to an additional reduction of bacterial levels after CMP. Our data corroborate previous findings from rDNA-based molecular studies [23,24]. Moreover, a high prevalence of rDNA positive samples after inter-appointment medication has been previously reported [22][23][24][25].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The rDNA-based analysis showed that the inter-appointment medication did not contribute to an additional reduction of bacterial levels after CMP. Our data corroborate previous findings from rDNA-based molecular studies [23,24]. Moreover, a high prevalence of rDNA positive samples after inter-appointment medication has been previously reported [22][23][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…Our data corroborate previous findings from rDNA-based molecular studies [23,24]. Moreover, a high prevalence of rDNA positive samples after inter-appointment medication has been previously reported [22][23][24][25]. An interesting finding of this study is that the rRNA-based analysis revealed the activity of bacteria detected by rDNA in S4 samples, proving it to be a useful strategy for monitoring the antibacterial effect of endodontic procedures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Entretanto, existem divergências entre os estudos moleculares que avaliaram a eficácia da medicação intracanal em promover redução de micro-organismos dos canais radiculares. Alguns autores relataram uma redução do número de cópias de rDNA após o uso da medicação intracanal (Paiva et al, 2013a;Provenzano et al, 2015;Nakamura et al, 2018); outros afirmaram não haver diferença entre o número de cópias de rDNA detectados após o preparo químicocirúrgico e aquele detectado após a medicação intracanal (Sakamoto et al, 2007;Blome et al, 2008;Siqueira, 2011b;Teles et al, 2014;Ferreira et al, 2015); enquanto outro autor identificou um aumento do número de cópias de rDNA após o uso da medicação intracanal (Zandi et al, 2016). Entretanto, vale ressaltar, que esses estudos moleculares baseados em rDNA apresentam uma limitação, que é a não distinção entre as células vivas e mortas Rôças, 2005;Loozen et al, 2011;Brudin et al, 2013).…”
Section: Introductionunclassified